Traditional medicine, environmental exposures, and cultural practices in cancer risk: insights from low- and middle-income countries - Miya, Thabiso Victor; Marima, Rahaba; Marutha, Tebogo; Luvhengo, Thifhelimbilu Emmanuel; Mkhize-Kwitshana, Zilungile; Chauke-Malinga, Nkhensani; Mazibuko, Gugulethu; Dlamini, Zodwa (Frontiers in Oncology, 2025)
Cancer is a growing public health concern in low- and middle-income countries (LMICs), influenced by cultural practices, environmental exposures, and dependence on traditional medicine in addition to biological risk factors. Evidence from peer-reviewed publications published between 2010 and 2025 was combined in this narrative review. According to studies, traditional and complementary medicine (T&CM) is used by 35% to 79% of cancer patients in LMICs, which frequently delays biomedical treatment and complicates care. Over 2.4 billion people use biomass fuels for household air pollution (HAP), which has been associated with a two- to three-fold increased risk of lung cancer, especially in women. Furthermore, tobacco smoking contributes to about 2.7 million new cases of cancer in less developed areas each year, highlighting ongoing exposure to avoidable dangers. Findings show that the cancer burden in LMICs is further exacerbated by poor food storage, alcohol use, pesticide exposure, unregulated consumer chemicals, and stigma. These cultural and environmental factors must be addressed in preventative initiatives in addition to biological therapy. Strengthening T&CM regulations, enhancing food safety, upholding alcohol and tobacco legislation, lowering exposures at work and in the home, and introducing culturally-based education to dispel stigma and myths are among the top priorities. This is a narrative review rather than a systematic one; the goal is to map thematic evidence throughout Africa, Asia, and Latin America, providing insights for policy design. Integrated, context-specific, and community-driven approaches are required to eliminate inequities and promote equitable cancer control in LMICs.